Neoadjuvant Chemotherapy Increasing Relevance in Cancer Management - Markman, Maurie M. (IntechOpen, 2013)
In the chapters of this excellent text, the authors have described advances in the neoadjuvant chemotherapeutic management of a number of tumor types. Based on the extensive experience with this management concept in breast cancer, several chapters are devoted to this important topic (Section 1). Section 2 deals with the administration of neoadjuvant chemotherapy in non-breast malignancies. Those who read and study the content of the chapters in this book will come away with a far greater understanding of the rationale supporting neoadjuvant chemotherapy, the existing evidence-based data regarding its use, limitations of the approach, and required future investigative efforts to learn how to optimize the benefits of this innovative management concept.